E-COMMERCE DAN WTO: VISUALISASI BIBLIOMETRIK ATAS TREN DAN POLA PENELITIAN GLOBAL - Santiago, Dicky; Kartikasari, Cynthia Yohanna; Prarono, Aluisius Hery (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
E-commerce has become an essential part of rapidly growing international trade, necessitating regulations to manage the emerging challenges and opportunities. This article aims to explore the literature on the role of the World Trade Organization (WTO) in creating a framework governing electronic commerce or e-commerce in the global market. The article adopts a bibliometric approach to understand patterns and trends in the literature on global trade governance by evaluating the academic impact of research and publications. This study utilizes Harzing’s Publish or Perish (PoP) application to collect data from Google Scholar for relevant scientific publications. Additionally, the study uses VOS Viewer to visualize the network of articles. From the 978 articles accessed using Harzing PoP, the clusters generated from the VOS Viewer application are seven: (1) organization, WTO member, (2) regulation framework, (3) digital trade, (4) international commerce, (5) digital divide, (6) strategy, (7) trade rule negotiation. This study contributes to the development of international trade theory, particularly e-commerce. PoP assists in performing ranking analysis based on the selected topics. Keywords: e-commerce, regulation, global economy, WTO.